Impact of Applying the CKD-EPI 2021 Formula Compared to CKD-EPI 2009 for the Calculation of Estimated Glomerular Filtration Rate in a Spanish Tertiary Hospital - Felipe De la Fuente García; Sara Esteve Poblador; Mario Ortuño Alonso (Turkish Journal of Nephrology, 2024)
Background: Throughout the years, the stage of chronic kidney disease (CKD) has been classifed according to the Kidney Disease: Improving Global Outcomes (KDIGO) guideline, using equations to calculate the estimated glomerular fltration rate (eGFR). The 2009 CKD-EPI equation is the one currently used, but there is a new version from 2021 that eliminates the race correction factor. In this study, we will compare both equations.